Characterisation of non-obese diabetic patients with marked insulin resistance identifies a novel familial partial lipodystrophy-associated PPARγ mutation (Y151C) - Visser, M. E.; Kropman, E.; Kranendonk, M. E.; Koppen, A.; Hamers, N.; Stroes, E. S.; Kalkhoven, E.; Monajemi, H. (Diabetologia, 2011)
Aims/hypothesis Familial partial lipodystrophy (FPLD) is a rare metabolic disorder with clinical features that may not be readily recognised. As FPLD patients require a specific therapeutic approach, early identification is warranted. In the present study we aimed to identify cases of FPLD among non-obese patients with type 2 diabetes mellitus and marked insulin resistance. Methods We searched the databases of three diabetic outpatient clinics for patients with marked insulin resistance, arbitrarily defined as the use of ≥100 U insulin/day, and BMI ≤ 27 kg/m 2 . In all patients, metabolic variables and anthropomorphic measurements were evaluated and DNA was sequenced for mutations in the genes encoding lamin A/C (LMNA), peroxisome proliferator-activated receptor γ (PPARγ) and cell death-inducing DFFA-like effector c (CIDEC). Results Out of 5,221 diabetic individuals, 24 patients fulfilled all criteria. Twelve patients were willing to participate, of whom five showed clinical features of lipodystrophy. In three of these patients the clinical diagnosis of FPLD was confirmed by the presence of mutations in LMNA or PPARG ; one patient harboured a novel heterozygous mutation (Y151C) in PPARG . The Y151C mutant displayed impaired DNA-binding capacity and hence reduced transcriptional activity compared with wild-type PPARγ. Dominant-negative activity was absent. Conclusion/interpretation The combination of BMI ≤ 27 kg/m 2 and the use of >100 U insulin/day increases the chance of identifying lipodystrophy. Thus careful assessment of clinical features of FPLD should be considered in these patients, allowing earlier therapeutic interventions.